Healthcare Consumerism and Patient Loyalty in the Age of Telehealth: An Exploratory Roadmap - Kwon, Ik-Whan G.; Kim, Sung-Ho (British Journal of Healthcare and Medical Research, 2023)
Customer loyalty is known as a source of sustained revenue steam and means of building and maintaining a strong relationship with customers for lifetime shopping experiences. Although there are a few studies in patient loyalty in healthcare fields, there is no theoretical or empirical studies on patient loyalty under the telehealth environment. This study, therefore, borrowed the framework from the commercial consumer loyalty model and build patient loyalty framework for healthcare practices in telehealth environment. There is a growing trend in both academic and industry circles that telehealth will stay as a one of the viable healthcare management alternatives even after Covid period. This study reviews the current status of patient loyalty based on the existing literature and explores a pathway to establish patient loyalty in telehealth platform.